A MODEL FOR THE IMPLEMENTATION OF RELIGIOUS MODERATION IN MADRASAH: Case Studies in Kediri and Surabaya - Titik Triwulan Tutik (UIN Sunan Kalijaga Yogyakarta, 2022)
This research is an Applied Research on National Strategic Studies, on the Implementation Model of Religious Moderation in Madrasahs by taking case studies in Surabaya City and Kediri Regency. Objectives of the activity: First, to analyze management patterns in implementing religious moderation in madrasas. Second, examine the application of subject teacher learning in implementing religious moderation in madrasas for their students. Third, describe the obstacles faced by madrasa institutions in implementing religious moderation. The research design is a field research design in which the researcher will conduct observations and interviews with the respondents on the issues raised. These findings will be analyzed using the social construction theory of Peter L. Berger.The results of the study show: First, the management pattern in implementing religious moderation in madrasas begins with determining the vision and mission of the madrasa, and preparing the madrasa work program, which is documented in the Madrasah Strategic Plan (Resntra), Madrasah Work Plan, Annual Activity Plan, Madrasah Activity Plan and Budget, and Madrasah Curriculum. Second, Madrasas in implementing religious moderation generally use three patterns, namely: (1) integrating with the learning process; (2) habituation activities; (3) through extracurricular. Based on the implementation model of religious moderation at the madrasah, it can generally be concluded that these patterns follow Peter L. Berger's Social Construction Theory, namely the existence of stages in implementation such as the preparation of vision and mission, work programs and habituation to the institution (process externalization), implementation of vision and mission, work programs, and habituation to madrasas (objectification process), and a correct understanding of moderation and implementation in everyday life both in the school, home, and community environment (internalization process).Based on the findings/results of the research, the suggestions/recommendations that can be given are: (1) there needs to be socialization, workshops, technical guidance, training on religious moderation for all educators and education personnel in Madrasahs to create a unified insight; (2) The government, in this case, the Ministry of Religion of the Republic of Indonesia needs to provide a separate budget related to religious moderation activities, especially in madrasas so that activities can be carried out massively, systematically, and structured from the main level to the madrasa level; and (3) Madrasahs need to coordinate with parents through the madrasa committee, and carry out MoUs with stakeholders such as national private companies through CSR programs in implementing religious moderation in madrasas so that activities can be carried out massively and planned.